2003
DOI: 10.1177/15353702-0322807-10
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Fatty Acids and Exercise on Body Weight Regulation and Metabolism in Female Wistar Rats

Abstract: High-fat diets made with different fats may have distinct effects on body weight regulation and metabolism. In the present study, the metabolic effects of high-fat (HF) diets made with fish oil, palm oil, and soybean oil were compared with a low-fat diet in female Wistar rats that were either exercised (EX, swimming) or that remained sedentary as controls. Each adult rat was exposed to the same diet that their dams consumed during pregnancy and lactation. When they were 9 weeks old, rats began an EX regimen th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 46 publications
4
21
0
1
Order By: Relevance
“…In summary, we observed that in normal Wistar rats, SO treatment induces insulin resistance and islet insulin secretion failure, which is in accordance with previous studies [2,20,34,35]. Furthermore, the impairment of GSIS observed (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In summary, we observed that in normal Wistar rats, SO treatment induces insulin resistance and islet insulin secretion failure, which is in accordance with previous studies [2,20,34,35]. Furthermore, the impairment of GSIS observed (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Lipids based on soybean oil (SO) are traditionally used as nutritional support for surgical or critical patients [31,32]. Some studies with normal rats on a SO diet reported an increase in body weight and fat gain as well as an impairment of glucose tolerance [33] and insulin resistance [34,35]. However, a rise of glucose-stimulated insulin secretion (GSIS) was also observed [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater leptin levels were found in weanling C57BL/J6 male mice fed high-fat diets (at 58 % of energy) based on beef tallow for 7 weeks than mice fed high-fat diets based on fish oil, safflower-seed oil or animals fed low-fat diets (at 10 % of energy); leptin levels were correlated with body fat as well (60) . Similar results were found in other studies (102,188) .…”
Section: Hormonessupporting
confidence: 93%
“…For example, forced treadmill running, water immersion and so on. 10,11 are perceived as psychological stress, 12 which may complicate interpretation of results. A preferred method is the use of running wheels in which rodents can run voluntarily.…”
Section: Introductionmentioning
confidence: 99%